Lamina–associated chromatin in the context of the mammalian genome folding - Ulianov, S.V.; Shevelyov, Y.Y.; Razin, S.V. (Вiopolymers and Cell, 2016)
Eukaryotic interphase chromatin is folded hierarchically. Mammalian chromosomes are partitioned into topo-logically associating domains (TADs) whose interactions with each other drive the spatial segregation of the bulk chromatin into A–compartment containing active genomic regions, and B–compartment harboring re-pressed genomic loci and gene deserts. The internal structure of TADs is represented by CTCF/cohesin–mediated loops. The specific local and large–scale spatial structure of chromosomes plays an important role in the regulation of the genome functions. The recruiting of the genome loci to internal nuclear structures drives a subset of long–range chromatin interactions. The nuclear lamina is found to be involved into chromatin spatial positioning within the nucleus. The chromatin–nuclear lamina interactions are not rigid allowing for a substantial reconfiguration of the genome topology in cell generations and during differentiation. Here, we review some resent findings shedding light on the nature and spatial dynamics of the lamina–associated genomic regions.